2002
DOI: 10.1046/j.1365-2648.2002.02365.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the use of developmental action inquiry in constructing a problem‐based learning curriculum for pre‐registration nursing education in Hong Kong: a student perspective

Abstract: The evaluation findings show that a paradigm shift from teacher-centred to student-centred learning, from valuing self-learning to co-operative group-learning, and from theory-based to practice-based learning occurred among the students. DAI was found to be an effective change strategy for transforming participants to become collaborators in searching for useful knowledge and coconstructing the PBL learning context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…The exception for a clear positive trend of learning experience among these students was the development of self-directed learning. One of the identified themes from this study, 'contrasting view in critical thinking', and a still more positive view towards 'self-directed learning through PBL', were comparable with the results of a developmental action inquiry (DAI) on constructing a PBL curriculum for pre-registration nursing education in Hong Kong (Pang et al, 2002). The themes suggest that there is a need to continue the work of developing critical thinking, better group facilitation, and communication skills.…”
Section: Comparing the Quantitative And Qualitative Datasupporting
confidence: 62%
“…The exception for a clear positive trend of learning experience among these students was the development of self-directed learning. One of the identified themes from this study, 'contrasting view in critical thinking', and a still more positive view towards 'self-directed learning through PBL', were comparable with the results of a developmental action inquiry (DAI) on constructing a PBL curriculum for pre-registration nursing education in Hong Kong (Pang et al, 2002). The themes suggest that there is a need to continue the work of developing critical thinking, better group facilitation, and communication skills.…”
Section: Comparing the Quantitative And Qualitative Datasupporting
confidence: 62%
“…Retrieving knowledge and applying it to a clinical setting is an important step to help a novice nurse to become an expert [8]. Rapidly advancing medical technology and science requires nursing education to become "hybrid, " combining old teaching methods with innovative methodologies [14]. Being an active learner and keeping abreast with current knowledge is a necessary trait for being a nurse.…”
Section: Pbl and Nursingmentioning
confidence: 99%
“…Papers by and VisschersPleijers et al (2005) state that no evidence exists with regard to PBL and dysfunctional groups, however a significant amount of literature is available on difficult groups described by teaching staff. Pang et al (2002) found attributes such as a lack of cooperation amongst students and also an ambivalence about whom they should develop learning group partnerships with. Pang et al (2002) also found that students tended to be too independent and spent too much time on self directed study, which offset their co-learning with fellow colleagues.…”
Section: Interaction Between Students and Group Dynamicsmentioning
confidence: 99%
“…Pang et al (2002) found attributes such as a lack of cooperation amongst students and also an ambivalence about whom they should develop learning group partnerships with. Pang et al (2002) also found that students tended to be too independent and spent too much time on self directed study, which offset their co-learning with fellow colleagues. They were also able to show that some students encountered difficulties in personality clashes.…”
Section: Interaction Between Students and Group Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation